O método lúdico-ambital: uma experiência de leitura criativa em sala de aula - Oliveira, Neusa Maria Jorgino (2008)
This work presents the ideas of Alfonso López Quintás related to his so called creative reading and the use of the Ludic Scope Method MLA. It also shows the results of the MLA method used with undergraduates at a Portuguese Language Course. His intention in performing the test was not only to see how the method works, but also to call the attention of the students to it and the possibility for further practice in other courses. As he encountered some difficulty to carry out the experiment, he just tested it with a small group of students. The results were somehow satisfactory and the indicators are part of the analysis that go with the pictures and reports of the experiment. It is necessary to provide young reader citizens with some methods and procedures to enable an easier process of reading. The MLA method can be one of these methods and, according to the study it is rich for the development of what Lopez Quintás calls creative reading .